Activity of acnistins against leishmania mexicana, trypanosoma cruzi and plasmodium falciparum - Chataing, Bernardo; Hocquette, Antoine; Diaz, Silverio; Valentin, Alexis; Usubillaga, Alfredo (Ciencia)
Acnistin A and E, two withanolides with a bicyclic side-chain at C-17, isolated from the leaves of Acnitus arborescens (L) Schlecht that grows in the Venezuelan Andes inhibited the growth of Leishmania mexicana and Trypanosoma cruzi in cultured medium. On the other hand acnistins A, E, and L, also inhibited the growth of a chloroquine-resistant strain and a chloroquine-sensitive strain of Plasmodium falciparum in cultured medium. Data indicated that acnistins exerted a higher inhibitory activity upon these parasites that ketoconazole, mevastatin and lapachol in the same conditions of assay. Â